Drama for Students : Presenting Analysis, Context, and Criticism on Commonly Studied Dramas. - Galens, David A., editor 652250; Gale Group (Online service) 651863 (Detroit : Gale, 2003)
Provides critical overviews of the most-studied plays of all time periods, nations, and cultures. Includes discussions of themes, characters, critical reception, dramatic devices and traditions as well as cultural and historical context.